2021
DOI: 10.24875/ciru.200008811
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico de las fracturas mandibulares en el servicio de urgencias

Abstract: Resultados: Se incluyeron 319 sujetos con fracturas mandibulares, jóvenes (32.5 años), con predominio del sexo masculino (89.7%), la mayoría desarrollaba algún oficio (64.2%), el 14.4% con alguna comorbilidad y el 76% presentaba alcoholismo al momento de la lesión. El sitio anatómico más afectado fue el ángulo mandibular, seguido de la parasínfisis. La causa más frecuente de lesión fue por agresión física. Conclusiones: Las fracturas mandibulares en nuestro servicio de urgencias suelen ser simples y afectar el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…Studies have reported a correlation between mandibular angle fractures and assault. 15 , 16 , 17 Seven patients in our study had undergone assault with six mandibular angle fractures in twenty mandibular angle fractures; these results revealed a strong association between assault and mandibular angle fracture.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Studies have reported a correlation between mandibular angle fractures and assault. 15 , 16 , 17 Seven patients in our study had undergone assault with six mandibular angle fractures in twenty mandibular angle fractures; these results revealed a strong association between assault and mandibular angle fracture.…”
Section: Discussionsupporting
confidence: 49%
“…According to previous studies, the epidemiology of mandibular fractures may be affected by geographic and population characteristics, such as demographic composition, laws, and types of transportation. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Wan Fang Hospital is located in a densely populated area with a diverse population in terms of age, career, and socioeconomic status. This district also contains many metro stations, highway exits, and motorcyclists.…”
Section: Discussionmentioning
confidence: 99%